Makna Ritual Dalam Risalah Tarekat Qodiriyah Naqysabandiyah - R Aris Hidayat (Balai Penelitian dan Pengembangan Agama Semarang, 2010)
Philological study to religious manuscripts is quite interesting because itis considered as a way to maintain a very highly-valued cultural heritage. Andthis research is a kind of such effort. This study examines the Risalah QadiriyahNaqsyabandiyah, an Islamic Javanese manuscript, which is preserved in theNational Library of Republic of Indonesia. Using philological and historicalmethods, this research is to edit the manuscript and to analyze its messages.In additions, this study is aimed to give significant contributions not only tothe Ministry of Religious Affairs of Republic Indonesia but also to public ingeneral.The result of the study says that according to the Risalah QadiriyyahNaqsyabandiyyah in the midst of the nineteenth century, there was a groupof people practicing the teachings of the Tarekat Qadiriyah Naqsyabandiyah.Their wirid, however, was different from either the Tarekat Qadiriyyah or theTarekat Naqsyabandiyah. The fact obviously shows that Islam in Java, accordingto the manuscript had a nuance of mysticism and syncretism.